Sense, reference, and philosophy - Katz, Jerrold J. (Oxford University Press, 2004)
Sense, Reference, and Philosophy develops the far-reaching consequences for philosophy of adopting non-Fregean intensionalism, showing that long-standing problems in the philosophy of language, and indeed other areas, that appeared intractable can now be solved. Katz proceeds to examine some of those problems in this new light, including the problem of names, natural kind terms, the Liar Paradox, the distinction between logical and extra-logical vocabulary, and the Raven paradox. In each case, a non-Fregean intentionalism provides a philosophically more satisfying solution.